2013
DOI: 10.5194/acp-13-9771-2013
|View full text |Cite
|
Sign up to set email alerts
|

Validation of XCO<sub>2</sub> derived from SWIR spectra of GOSAT TANSO-FTS with aircraft measurement data

Abstract: Abstract. Column-averaged dry air mole fractions of carbon dioxide (XCO2) retrieved from Greenhouse gases Observing SATellite (GOSAT) Short-Wavelength InfraRed (SWIR) observations were validated with aircraft measurements by the Comprehensive Observation Network for TRace gases by AIrLiner (CONTRAIL) project, the National Oceanic and Atmospheric Administration (NOAA), the US Department of Energy (DOE), the National Institute for Environmental Studies (NIES), the HIAPER Pole-to-Pole Observations (HIPPO) program… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
68
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 65 publications
(69 citation statements)
references
References 63 publications
1
68
0
Order By: Relevance
“…XCO 2 has a seasonal amplitude of approximately 7-12 ppm at mid-latitudes over the Northern Hemisphere. In this study, the growth rate of uncorrected GOSAT XCO 2 was roughly 2.5 ppm yr −1 from 2009 to 2013, while Inoue et al (2013) showed that the growth rate of aircraft-based XCO 2 at most sites was about 2.0 ppm yr −1 from 2007 to 2010. This is consistent with the rapid increase of CO 2 emissions over the last few years.…”
Section: Temporal Behaviors Of Uncorrected/correctedmentioning
confidence: 51%
See 2 more Smart Citations
“…XCO 2 has a seasonal amplitude of approximately 7-12 ppm at mid-latitudes over the Northern Hemisphere. In this study, the growth rate of uncorrected GOSAT XCO 2 was roughly 2.5 ppm yr −1 from 2009 to 2013, while Inoue et al (2013) showed that the growth rate of aircraft-based XCO 2 at most sites was about 2.0 ppm yr −1 from 2007 to 2010. This is consistent with the rapid increase of CO 2 emissions over the last few years.…”
Section: Temporal Behaviors Of Uncorrected/correctedmentioning
confidence: 51%
“…To calculate aircraft-based XCO 2 and XCH 4 (as described in the next paragraph), we also used tower data from the Meteorological Research Institute (MRI) in Tsukuba (Inoue andMatsueda, 1996, 2001) and the NOAA ESRL/GMD tall tower network in Park Falls, WI and West Branch, IA . Details of the aircraft and tower measurements are described in Inoue et al (2013) and Inoue et al (2014), except for the JMA aircraft and groundbased measurements. The JMA aircraft measurements are conducted by utilizing the cargo aircraft C-130H of the Japan Ministry of Defense (MOD) to collect flask air samples once a month during a regular flight between the mainland of Japan and Minamitorishima, an island located nearly 2000 km southeast of Tokyo (Tsuboi et al, 2013).…”
Section: Aircraft-based Datamentioning
confidence: 99%
See 1 more Smart Citation
“…Geographical colocation methodology is perhaps the most popular colocation methodology due to its simplicity and straightforwardness. Examples of geographical coincident criteria include selecting all same-day satellite observations falling within ±5 • of a location of interest (Inoue et al, 2013), selecting data falling within ±30 min from about 0.5 to 1.5 • rectangles centered at each validation site (Morino et al, 2011), selecting data within 5 • and ±2 h (Butz et al, 2011;Cogan et al, 2012), selecting observations within a 10 • × 10 • lat-long box (Reuter et al, 2013), and selecting weekly data that fall within a 5 • radius of a validation site (Oshchepkov et al, 2012). For the performance comparison in this section, we define a geographical colocation methodology by averaging all same-day satellite observations falling within 500 km of a location of interest.…”
Section: Comparison To Existing Methodologiesmentioning
confidence: 99%
“…Geographical colocation typically defines a spatiotemporal neighborhood region, also known as a coincidence criterion, around the location of interest and then take summary statistics (e.g., mean or median). Examples of geographical colocation includes averaging all same-day satellite observations falling within ±5 • of a location of interest (Inoue et al, 2013), averaging all observations falling within 5 • and ±2 h , and taking the monthly median of all observations within a 10 • × 10 • lat-long box (Reuter et al, 2013). More sophisticated colocation methodologies add other correlated geophysical covariates in constructing such "neighborhoods" under the principle that conditioning on these additional correlated covariates would improve the quality of the comparison.…”
Section: Published By Copernicus Publications On Behalf Of the Europementioning
confidence: 99%